2022
DOI: 10.1007/s12144-022-03424-0
|View full text |Cite
|
Sign up to set email alerts
|

Negative implicit in-group stereotypes of Chinese male drug abusers: evidence from ERP

Abstract: Psychological dependence is the most important factor leading to relapse, few studies have examined whether in-group stereotypes exist in drug abusers, while it's helpful for drug abusers in getting rid of psychological dependence. To investigate the presence of in-group stereotypes and the neural mechanisms in drug abusers, two experiments were designed in this study. Experiment 1 used a classification–verification paradigm and Experiment 2 used The Extrinsic Affect Simon Task (EAST), simultaneous collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…Similarly, some research has uncovered that the violation of social information, such as social norm (Mu, Kitayama, Han, & Gelfand, 2015), and social con icts (Huang, Kendrick, & Yu, 2014), would elicit a larger N400. In addition, empirical studies have found that stereotypes, including in-group (Zeng et al, 2022) and rural migrant worker stereotype (Wang et al, 2011), is no exception to this result, suggesting that violation of stereotype does trigger an N400 amplitude (Wang et al,2017). Thus, the N400 component may be used as an indicator of pro-thin and pro-fat implicit preference of cognitive neural mechanisms in individuals with implicit weight-stereotypical bias.…”
Section: Eeg Indicators: N400mentioning
confidence: 96%
“…Similarly, some research has uncovered that the violation of social information, such as social norm (Mu, Kitayama, Han, & Gelfand, 2015), and social con icts (Huang, Kendrick, & Yu, 2014), would elicit a larger N400. In addition, empirical studies have found that stereotypes, including in-group (Zeng et al, 2022) and rural migrant worker stereotype (Wang et al, 2011), is no exception to this result, suggesting that violation of stereotype does trigger an N400 amplitude (Wang et al,2017). Thus, the N400 component may be used as an indicator of pro-thin and pro-fat implicit preference of cognitive neural mechanisms in individuals with implicit weight-stereotypical bias.…”
Section: Eeg Indicators: N400mentioning
confidence: 96%
“…The development of pharmaceutical technology has led to an increase in the variety, forms, and functions of drugs. However, the misuse of drugs such as opium, heroin, methamphetamine, and morphine can result in severe physical and mental dependence [ 1 ]. Drug abuse can cause damage to various organ systems, including the nervous system, cardiovascular system, and respiratory system [ 2 ].…”
Section: Introductionmentioning
confidence: 99%